Does CSRD and GCG moderate the effect of Financial Performance on Stock Return? - Nurfadila Nurfadila; Sukmayanti Sukmayanti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
The purpose of this study is to examine and analyze the effect of financial performance on stock returns with good corporate governance and disclosure of corporate social responsibility as moderating variables in plantation companies listed on the Indonesia Stock Exchange (BEI) 2017-2019 period. They determined the sample in this study using a purposive sampling method to obtain 12 companies following the criteria of a predetermined model, data collection techniques in research using documentation studies by analyzing financial reports and sustainability reports of research samples. This study uses a quantitative approach with moderated regression analysis to test good corporate governance and disclosure of social responsibility in mediating the effect of financial performance on stock returns. The measurement of financial performance uses financial ratios, namely return on equity. The test results show that economic performance has a positive and significant effect on stock returns. Institutional ownership and CSR disclosure can moderate the impact of financial performance on stock returns. The proportion of independent commissioners, managerial ownership, and audit committee cannot moderate stock returns' financial performance.